OPTIMIZATION OF TURNING PROCESS PARAMETERS, ON EN 9 CARBON STEEL USING GREY RELATIONAL ANALYSIS - B. PADMA; B. SATISH KUMAR; N. GOPIKRISHNA (International Journal of Innovations in Engineering Research and Technology, 2021)
Present paper entails the optimization of the machining process parameters for the turning of EN 9 carbon steel (it is acarbon steel, also known as 070m55, available in diameters, flats, squares and plates –it can be used for gears, sprockets and cams) on the lathe machine using a combination of the Taguchi and the Grey Relational Analysis to yield a minimum cutting forcesand expected minimum surface roughness. Process parameters chosen are as the rotational speed, a feed, the depth of cut and a selected cutting fluid. The experiments which are conducted as per the Taguchi experimental designs and the L9orthogonal array were carried outin the experiment. The Analysis of variance (ANOVA) has also been used to evaluate the most impactof processing parameterswhich were resulted in the experiment. The reversionequations were also been established between a process parameters &the responses. The results that indicate the depth of cut is an important factor on that affecting acutting force & the surface roughness assessed by thefeed, a speed and the cutting fluid.